Active Transposition of Insertion Sequences by Oxidative Stress in Deinococcus geothermalis - Lee, Chanjae; Choo, Kyungsil; Lee, Sung-Jae (Frontiers in Microbiology, 2020)
Radiation-resistant bacterium Deinococcus geothermalis has a total of 73 insertion sequences (ISs) in genomes, and some of them are actively transposed to other loci with replicative mode due to oxidative stress of hydrogen peroxide treatment. Here, we detected two transposition events in wild-type (WT) strain and LysR family member gene disrupted strain (Δdgeo_2840). Similar to our previous report (Lee et al., 2019), phytoene desaturase (dgeo_0524), a key enzyme of carotenoid biosynthesis, was disrupted by the integration of IS element, thereby detected a single phenotypically non-pigmented colony in each WT and Δdgeo_2840 strain. Two separate types of IS element have been integrated into non-pigmented clones: ISDge11 for WT and ISDge6 for Δdgeo_2840 strain. Surprisingly, Δdgeo_2840 mutant strain revealed higher resistance to oxidative stress than WT strain at late exponential growth phase. From the qRT-PCR analysis, OxyR (dgeo_1888) was highly up-regulated to 30-fold by oxidative stress through hydrogen peroxide treatment in both WT and Δdgeo_2840 mutant strains. However, the oxidative stress response enzyme, catalase or superoxide dismutase, was not significantly induced by overexpressed OxyR. Thus, a putative LysR family regulator Dgeo_2840 controlled the expression of ISDge6 type transposase and the induction of OxyR under oxidative condition. There is LysR family DNA-binding protein dependent active transposition of specific type IS and the up-regulated OxyR has not positively controlled ROS scavenger enzymes in D. geothermalis.